Jednostronnie profesjonalne umowy pośrednictwa handlowego a regulacja kodeksu cywilnego o umowie agencyjnej i umowie zlecenia — uwagi na tle wybranych umów - Wójtowicz, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Contracts on provision of mediation services similar to agency contracts are commonly concluded in commercial trade. It is potentially possible to apply Civil Code provisions on a contract of mandate to unilaterally professional mediation contracts. However, many elements make these contracts similar to agency contracts rather than contracts of mandate. In consequence the application of Civil Code provisions on agency contracts should be considered, bearing in mind that some of the provisions are specific for agency contracts only, such as provisions linked to the bilaterally professional character of agency contracts and provisions related to the fact that an agency contract creates a long-term relationship.
Keywords: commercial mediation; agency contract; contracts for the provision of services; entrepreneur